2009
DOI: 10.1149/1.3205520
|View full text |Cite
|
Sign up to set email alerts
|

Status of Hexis SOFC Stack Development and the Galileo 1000 N Micro-CHP System

Abstract: Hexis is developing the micro-CHP SOFC-system Galileo 1000 N. Field tests with the Galileo 1000 N were started and at present 17 systems are installed in the field. Additional 13 systems are installed at Hexis' labs. In a system test with improved cells, an electrical power output of more than 1000 W (AC, net), an electrical efficiency of more than 40% (DC) and 36% (AC, net) could be achieved, while another test showed a total efficiency of more than 90% (LHV). One of the lab systems runs now for more than 150… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…However, sulfur-containing impurities in most prospective SOFC fuels such as natural gas and biogas inevitably lead to considerable performance drops upon exposure to Ni-based anodes. Sulfur poisoning of the most commonly used Ni/YSZ cermet anodes has been widely investigated, both experimentally and theoretically, and was related to the Ni surface poisoning with elemental sulfur. However, only a few studies have targeted the sulfur poisoning behavior of Ni/CGO anodes, although they are used in several commercial applications and have been shown to possess a significantly higher sulfur tolerance than Ni/YSZ. Hydrogen oxidation on Ni/CGO was frequently assumed to proceed via the same reaction mechanism as on Ni/YSZ, where hydrogen spillover including electrochemical charge transfer at the triple-phase boundary (TPB) between Ni/YSZ/gas phase was shown to be the rate-limiting step. However, recent studies of Ni/CGO have suggested that the rate-determining charge transfer reaction is likely to happen at the CGO/gas-phase double layer (DPB) rather than at the TPB between Ni/CGO/gas phase.…”
Section: Introductionmentioning
confidence: 99%
“…However, sulfur-containing impurities in most prospective SOFC fuels such as natural gas and biogas inevitably lead to considerable performance drops upon exposure to Ni-based anodes. Sulfur poisoning of the most commonly used Ni/YSZ cermet anodes has been widely investigated, both experimentally and theoretically, and was related to the Ni surface poisoning with elemental sulfur. However, only a few studies have targeted the sulfur poisoning behavior of Ni/CGO anodes, although they are used in several commercial applications and have been shown to possess a significantly higher sulfur tolerance than Ni/YSZ. Hydrogen oxidation on Ni/CGO was frequently assumed to proceed via the same reaction mechanism as on Ni/YSZ, where hydrogen spillover including electrochemical charge transfer at the triple-phase boundary (TPB) between Ni/YSZ/gas phase was shown to be the rate-limiting step. However, recent studies of Ni/CGO have suggested that the rate-determining charge transfer reaction is likely to happen at the CGO/gas-phase double layer (DPB) rather than at the TPB between Ni/CGO/gas phase.…”
Section: Introductionmentioning
confidence: 99%
“…3 The good scalability, from stacks producing a few kW up to several MW, makes this technology very exible in terms of its applications, ranging from decentralised domestic electricity and heat generation to power plant scale energy production. 2,4,5 Due to their excellent performance in hydrogen fuel, Ni/YSZ cermets are the state-of-the-art anodes for both electrolyte as well as anode supported cell designs. However, they still suffer from some drawbacks, such as Ni agglomeration at high temperatures, 6 coking when using hydrocarbon fuels under low steam to carbon ratios, 7 sulphur poisoning, 8,9 and especially instability upon redox cycling (cyclic reduction and oxidation).…”
Section: Introductionmentioning
confidence: 99%
“…Since the conductivity of electrolytes has an exponential dependence on temperature [ 13 ], operating temperatures above 800 °C are required to achieve high specific power. Nevertheless, even now, the electrolyte supported design is popular among SOFC manufacturers [ 82 , 83 , 84 ].…”
Section: Classification Of Sofcmentioning
confidence: 99%